2016
DOI: 10.1177/204380871600700301
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Special Issue: Understanding the Role of Attentional Control in the Development of Anxiety in Childhood, Adolescence and across the Lifespan

Abstract: Anxiety is characterised by a distinctive emotional, cognitive and behavioural symptomatology. The central emotional symptoms are fear and apprehension, often evoked by the occurrence or anticipation of specific types of situations; the primary cognitive symptoms are negative thoughts and worries concerning the uncertainties and potential threats associated with such situations; and the main behavioural symptom is avoidance or attempted avoidance of these situations (Grills, Seligman & Ollendick, 2014). People… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 120 publications
1
8
0
Order By: Relevance
“…This finding is consistent with the compensatory role of WM outlined by theoretical frameworks of anxiety and cognition (Derakshan Eysenck, 2009;Eysenck Derakshan, 2011;Eysenck et al, 2007), which suggest that the impact of anxiety on attentional control may be most evident in individuals with limited WM resources. The interaction between IU and WMC also fits with a broader pattern of results which highlight the importance of attentional control and WM in understanding the cognitive effects of anxiety and suggest a protective role for these factors that moderates the impact of elevated anxiety on cognitive processing (Booth, Mackintosh, Sharma, 2017;Hadwin, Visu-Petra, Muris, Derakshan, MacLeod, 2016;Matthew Owens, Stevenson, Hadwin, Norgate, 2014).…”
Section: Introductionsupporting
confidence: 68%
“…This finding is consistent with the compensatory role of WM outlined by theoretical frameworks of anxiety and cognition (Derakshan Eysenck, 2009;Eysenck Derakshan, 2011;Eysenck et al, 2007), which suggest that the impact of anxiety on attentional control may be most evident in individuals with limited WM resources. The interaction between IU and WMC also fits with a broader pattern of results which highlight the importance of attentional control and WM in understanding the cognitive effects of anxiety and suggest a protective role for these factors that moderates the impact of elevated anxiety on cognitive processing (Booth, Mackintosh, Sharma, 2017;Hadwin, Visu-Petra, Muris, Derakshan, MacLeod, 2016;Matthew Owens, Stevenson, Hadwin, Norgate, 2014).…”
Section: Introductionsupporting
confidence: 68%
“…Developmental research has highlighted that attentional control skills, including working memory (WM), are positively linked to several indices of adjustment in childhood and adolescence, such as emotion regulation (reviews by Hadwin et al, 2016;Moran, 2016). In addition, research has shown that performance in WM tasks in children and adolescents is positively associated with educational achievement in core subjects, including text comprehension and reading (e.g., Daneman and Carpenter, 1980;Perfetti, 1985;Baddeley, 1986) and mathematical problem solving (e.g., Bull and Scerif, 2001;Swanson and Beebe-Frankenberger, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several attentional and learning processes have been found to play a major role in pathological anxiety (i.e., anxiety disorders). Recent research suggests that attentional control (AC) and fear extinction learning feature prominently among such processes (e.g., Bar-Haim et al, 2007 ; Cisler and Koster, 2010 ; Eysenck and Derakshan, 2011 ; Milad and Quirk, 2012 ; Heeren et al, 2013 ; VanElzakker et al, 2014 ; Duits et al, 2015 ; Hadwin et al, 2016 ). In this study, we explore the possible association between these two processes.…”
Section: Introductionmentioning
confidence: 99%
“…Deficient AC has been found to characterize both clinical ( Olatunji et al, 2011 ) and subclinical anxiety (e.g., Fajkowska and Derryberry, 2010 ; Sportel et al, 2013 ). Such deficits may also account for the attention bias to threat commonly observed in anxious individuals ( Hadwin et al, 2016 ). Moreover, such deficits are associated with reduced ability to regulate emotion ( Fajkowska and Derryberry, 2010 ; Armstrong et al, 2011 ; Tortella-Feliu et al, 2014 ; Hsu et al, 2015 ; Morillas-Romero et al, 2015 ; O’Bryan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation